Rethinking the concept of 'subaltern-researcher': different D/deaf identities and communicative modalities as conflict factors in in-depth interviews. (August 2022) - Bitman, Nomy
This article focuses on the communicative, cultural, and practical aspects of being a hard-of-hearing (HH) researcher who studies D/deaf people's smartphone use through 20 in-depth interviews. This context presents the conflict between seeing deafness as a disability and seeing Deaf people as members of a cultural minority. This complexity of 'subaltern-researcher' concept combines with the limitations caused by conducting research as a marginal member of the academy, which in turn prompts the researcher's conflict between the commitment to marginalized research participants and the able-bodied academic obligation to act according to able-bodied research, analysis, and standards for publication of findings. This paper suggests a reflexive description of identity, culture, senses, and communication, which interacts with the social responsibility of the disabled researcher, and the interviewees' expressed agency. As such, this article contributes methodological and communicative insights on inclusive qualitative methods regarding both disabled participants and researchers.